Surgical treatment of epirethinal fibrosis: a current state of the problem - S.A. Kochergin; D.G. Alipov (РМЖ "Клиническая офтальмология")
S.A. Kochergin, D.G. Alipov Russian Medical Academy of Continuous Professional Education, Moscow This review discusses different approaches of surgical treatment of epiretinal fibrosis in detail. The introduction briefly describes the risk factors and causes of the disease. Each type of operation is analized as well as all the possible options. The results of 25 and 27G vitrectomy are compared, also in this review you can find the comparison of membrane removal without vitrectomy and after subtotal vitrectomy. When ERM is removed without vitrectomy, the risk of cataract appearing, retinal detachment, appearance of visual field defects decreases, but the risk of recurrence of the disease increases. In this article are also given the advantages and disadvantages of ILM-removing during the operation. In particular, the data of meta-analysis is described, that shows that patients’ who ERM was removed together with ILM visual acuity is higher 6 months after surgery, but after 18 months the situation becomes reverse. The possibilities for visualization of ERM during the operation are described. The article describes the features for visualization of ERM during surgery and a comparison of the results of operations involving ERM staining with ILM-Blue and MembraneBlue-Dual. The role of OCT in the diagnostics and treatment of ERF is shown. The possible surgery complications, such as hemophthalmia, retinal perforation, cataract, ocular hypertension, visual field defects are analized. This material does not include information about treatment of full macular hole. Key words: epiretinal fibrosis, epiretinal membrane, vitrectomy, optical coherence tomography, internal limiting membrane, complications, intraocular hemorrhage, retinal detachment, cataract, ocular hypertension, dyes, visual field. For citation: Kochergin S.A., Alipov D.G. Surgical treatment of epirethinal fibrosis: a current state of the problem // RMJ “Clinical ophthalmology”. 2018;1:55–59.